Inequality, firms, ownership and governance - Mayer, C (Oxford University Press, 2024)
Levels of productivity have been low in the UK since the financial crisis of 2008 for two reasons. First, the UK has a highly centralized banking sector that provides predominantly short-term working capital. As a result, small- and medium-sized enterprises are dependent on equity sources to fund their creation and expansion that are not readily available outside of London. Second, ownership of listed companies in the UK is exceptionally dispersed amongst global short-term asset management firms. This has had adverse consequences for productivity and inequality within as well as between firms and regions.